Implementasi Pemeriksaan Keimigrasian di Atas Alat Angkut Barang Pada Masa Pandemi Covid-19 di Kantor Imigrasi Kelas I Tpi Kendari - Prytha Yunir Omar Azhari Atiri Laode; Seno Setyo Pujonggo; Rita Kusuma Astuti (Peneliti.net, 2022)
The Class I Immigration Office of TPI Kendari carries out its Immigration duties, specifically the Clearance of marine transportation equipment in the waters of Southeast Sulawesi, however, with the latest regulations issued by the Covid-19 Task Force in Circular Letter Number 15 of 2022 concerning Health Protocols for Overseas Travel The 2019 Corona Virus Disease (COVID-19) pandemic explained that foreigners who were exposed to the Covid virus could be quarantined with a record of doing quarantine with self-financing and must show proof of payment confirmation for booking quarantine accommodation from the accommodation provider while in Indonesia. The purpose of the study was to determine the implementation of inspection/clearance on water conveyances during the covid-19 pandemic and to find out what obstacles were faced by immigration officials when conducting inspections/clearance on water conveyances during the covid-19 pandemic. This research was conducted. to improve information on the Loss and Benefits of the latest regulations issued by the Covid-19 Task Force in handling foreign transport crew members during the Covid-19 pandemic. The method used is a qualitative method, the data obtained is by conducting interviews with structural officials and employees at the Kendari class Immigration Office, then observations are made to find out and observe directly the handling of transport crews affected by the Covid-19 virus outbreak at the Class Immigration Office. I Kendari.